2012
DOI: 10.1016/j.biomaterials.2011.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Activation of pluripotency-associated genes in mouse embryonic fibroblasts by non-viral transfection with in vitro-derived mRNAs encoding Oct4, Sox2, Klf4 and cMyc

Abstract: a b s t r a c tThe first successful reprogramming of differentiated cells to a pluripotent state was done by retroviral introduction of four transcription factors (Oct4, Sox2, Klf4, cMyc) by the group of Yamanaka in 2006. Since then, scientists all over the world have attempted various methods to avoid insertional mutagenesis, a major limitation of the retrovirus-based method, however no technique was found to completely avoid DNA integration. Recently, a non-viral mRNA-based approach, inherent to avoid genomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Lipofection is carried out by fusion with cell membrane made up of phospholipid bilayer to deliver molecular cargo to the cells (Figure 4B). For instance, cationic lipid-mediated introduction of mRNAs encoding Yamanaka factors was reported in 2010 and 2011 [46, 47]. A proof-of-concept study determined that fibroblasts converted to less mature cardiomyocytes via direct reprogramming using lipid based miRNA methods as well [48].…”
Section: Non-viral Methods For Reprogramming To Pluripotency and Dmentioning
confidence: 99%
“…Lipofection is carried out by fusion with cell membrane made up of phospholipid bilayer to deliver molecular cargo to the cells (Figure 4B). For instance, cationic lipid-mediated introduction of mRNAs encoding Yamanaka factors was reported in 2010 and 2011 [46, 47]. A proof-of-concept study determined that fibroblasts converted to less mature cardiomyocytes via direct reprogramming using lipid based miRNA methods as well [48].…”
Section: Non-viral Methods For Reprogramming To Pluripotency and Dmentioning
confidence: 99%
“…Many in vitro transfection studies have revealed that although mRNA enabled even higher efficiency of protein expression than plasmid DNA (pDNA) within several hours after mRNA introduction into cells, the duration of expression was apt to be very short [12], [13]. For example, several groups recently induced pluripotent stem cells (iPSCs) by transfection of mRNA encoding Yamanaka factors [14], [15], [16]. Their success strongly suggests the feasibility of using mRNA for therapeutic purposes in the future; however, they generally performed repeat transfections with intervals of a few days, suggesting that the instability of mRNA hampered the durable protein expression after mRNA transfection.…”
Section: Introductionmentioning
confidence: 99%
“…Although they were able to generate iPSCs, initial conditions required 1 month of retrovirus treatment (several rounds) to generate a few colonies. On the other hand, there have been a few reports of generating reprogrammed cells using nanoparticles; however fibroblasts were used in most cases [30,38]. Interestingly, one group reported the use of magnetic nanoparticles to introduce plasmids to cells non-virally [30].…”
Section: Discussionmentioning
confidence: 99%